Comparison between the Bridges Evaluation Program “e-Bridge” in Costa Rica and the Bridge Management System in Czech Republic - Ramírez-Alméciga, Cristian A. (2016)
The only project that is taking place in the country in the field of bridges evaluation, The Bridges Assessment Program, is in charge of “e-Bridge”, and belongs to it. In order to determine whether the program is creating a solid base in Costa Rica or not for an integrated bridge management system, in the future, similar to those in European countries,  procedures and information of this program were compared with the corresponding ones in a more developed model: the Bridge Management System, in the Czech Republic. It was concluded that in the phases of inventory and visual inspections, the Bridges Assessment Program greatly resembles two of the four modules run by the Czech system. Although it was not possible to make any comparison with the two remaining modules of the Czech system, because in Costa Rica so far they are in development stage, two factors were found that could improve the costa rican project: the encoding of each of the members of the bridges to facilitate management of the information, and the development of software for  future storage of data relating to the history of maintenance and repair of bridges.